The Effect of Internship Experience, Work Interest, And Soft Skills on Students' Work Readiness in Sharia Insurance - Ningsih, Nur Widya; Sri Ramadhani; Yusrizal (LP2M IAIN Palopo, 2025)
This study aims to analyze the influence of internship experience, work interest, and soft skills on the work readiness of students in the Sharia Insurance Study Program, Faculty of Economics and Islamic Business, State Islamic University of North Sumatra. This study uses a quantitative approach with multiple linear regression method. The population in this study consists of 149 students from the 2020 and 2021 cohorts, with a sample size of 60 respondents obtained using the Slovin formula. Data analysis techniques utilize SPSS version 26 and EViews 10. The results of the study indicate that the variables of work interest and soft skills have a positive and significant effect on students' work readiness, while internship experience does not have a significant effect. Simultaneously, these three variables contribute 67.9% to students' work readiness. This study emphasizes the importance of developing soft skills and enhancing work interest in preparing students for the workforce, particularly in the Islamic insurance sector.